Extinction or survival ? Behavioral flexibility in response to environmental change in the African striped mouse Rhabdomys - (:unkn) unknown (My University, 2013)
The rapid rate of anthropogenic-related climate change is expected to severely impact ecosystems and their constituent organisms, leading to mass extinction. A rapid adaptive response of animals to such change could be due to reversible phenotypic flexibility, including behavioral flexibility. Our model, the African striped mouse Rhabdomys, is a small rodent widely distributed in southern Africa. The desert-living species R. pumilio displays social flexibility, whereby individuals switch their social organization in response to prevailing conditions, potentially allowing for persistence in rapidly changing environments. Individuals of the species from the moist grasslands (R. dilectus) show some flexible traits, but opportunities to utilize this potential are apparently not realized. The climate in southern Africa is predicted to become drier, making both desert and grassland species vulnerable to environmental change. Based on realized or potential social flexibility in striped mice, we provide three (not mutually exclusive) scenarios that consider: (i) extinction of the desert species as its habitat changes; (ii) range expansion and utilization of pre-existing adaptations of the desert species to displace the current grassland species; and (iii) grassland species exploiting their potential flexibility (behavioral adaptation) and surviving in their current habitat. Behavioral flexibility is costly but could allow species to persist in rapidly changing environments.
Keywords: African Research